Прогностичка вредност серумске ПАФ-АХ и протеина сличног висинину 1 за лошу прогнозу код пацијената са хипертензивном интрацеребралном крварењем: Серум ПАФ-АХ и протеин сличан висинину 1 код хипертензивне интрацеребралне хеморагије - Bai, Yaqiang; Wei, Man; Yang, Zhikun; Bu, Fanyan; Wang, Ziyang; Zhu, Binfeng; Zhu, Zuolei (Journal of Medical Biochemistry, 2026)
Objective To determine if serum levels of retinoid protein-like protein 1 (VILIP-1), Platelet-Activating Factor Acetylhydrolase (PAF-AH), and 8-hydroxydeoxyguanosine (8-OHDG) are prognostic of a poor prognosis in patients with hypertensive intracerebral hemorrhage.Methods The 194 patients in the cerebral hemorrhage group were hospitalized for hypertensive cerebral hemorrhage between January 2022 and January 2024.   Forty-five healthy individuals who underwent concurrent physical examinations at the hospital were selected to form the healthy control group. To observe the differences in the levels of serum PAF-AH, VILIP-1 and 8-OHDG, the relationship with the amount of intracerebral hemorrhage, the severity of intracerebral hemorrhage and poor prognosis, and how effectively it predicts the bad outcome of patients suffering from hypertensive intracerebral hemorrhage.Results Serum PAF-AH, VILIP-1, and 8-OHDG levels were substantially greater in the brain hemorrhage group than in the healthy control group (P
Keywords: Хипертензија; Церебрална крварења; Оптоепротеин-слична протеин 1; 8-хидроксидеоксигуанозин; Фактор активирања тромбоцита ацетилхидролаза